The Climax of Grain Mills Problems in Kirkuk and their Political and Economic Effective Dimensions - Aswad Al- Ahbab, Nassif Jassem; Abdul- Jubouri, Yasser Hamad Khalaf (Journal of Tikrit University for Humanities, 2023)
The problems of industry in Iraq in general are among the problems that cast a shadow over the economic and political reality. Since every industrial problem has dimensions and motives that led to the emergence of that problem, it may be fabricated or as a result of the course of other events that affect the reality of the industry in general, especially that the industrial problems in Kirkuk governorate are an extension of the industrial problems affecting all parts of Iraq, and the political and economic dimensions are One of the first dimensions is an impact on the grain milling facilities in Kirkuk governorate, which affects the functioning of these mills and the process of supplying the ration card with the product, 7 which in turn reaches the citizens, as it maintains the balance of market prices, and its shortage leads to higher prices, which would affect On the strength of the citizens, as it pushes matters to other curves, and opens the door to political quarrels in this regard, especially since many parties benefit from any imbalance that occurs to intervene to expand the mass base and interfere in economic matters due to the close interrelation between them, and the stability of these economic and political dimensions means the stability of the industry generally .